Perubahan penggunaan/ tutupan lahan dan prediksi perubahan penggunaan/ tutupan lahan di Kabupaten Lampung Selatan - Widiatmaka; Iskandar Lubis; Rakhman Adhiatma (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Land cover/land use is one of factors which is important in land management. The changes of land cover can affect on the polcy in an area. Land cover/land use of South Lampung Regency is potentially changes. Economy, social, and population are factors that affect the change in land cover. The aim of this research were to analyze spatial change of land cover/land use in South Lampung Regency period 2007-2019 and predicting future land cover/landuse of 2031. Analysis was carried out applying Cellular automata markov chain of land cover spatial model. The result showed that Kappa for image classification was 0.86. Dominant land cover type in South Lampung Regency was plantation field of 35.47 – 36.18%. Model validation of 2031 predicted land cover was 0.946, while The types of land cover that increase in 2031 were built up area and paddy field of 96.8% and 86.5%, respectively, while paddy fields, forest, moor, body of water, plantation, shurb were decreasing approximately 16.2, 14.9, 13, 7.7, 4.1 and 1.0%. Paddy field that had the most area of decline as prediction results of 16.2%.